Green brand benefits and their influence on brand loyalty. Issue 3 (2nd May 2017) - Lin, Jialing; Lobo, Antonio; Leckie, Civilai
Abstract : Purpose: The purpose of this paper is to investigate the formation of green brand image through customers' perceptions of the functional and emotional benefits associated with green brands and the influence of green brand image on purchase behavioural response. Additionally, the influence of a moderating variable (green perceived risk) on this formation process is examined. Design/methodology/approach: Data were collected using an online survey administered to a consumer panel in China. Structural equation modelling was used to test the conceptual model. Findings: The results demonstrate that the provision of utilitarian benefits and self-expressive benefits directly enhance the brand's green image. Also, utilitarian benefits and green brand image have direct influences on green brand loyalty. Green perceived risk negatively moderates the relationship between utilitarian benefits and green brand image. Research limitations/implications: This study extends previous research by examining the development of green brand image and investigating the moderating role of green perceived risk in this process. Also, this study enriches research on green brand and corporate branding by investigating the relationship between green brand image and brand loyalty. Originality/value: Although previous research has examined how perceived benefits influence the development of corporate brand image, the issue has not been investigated from a green branding perspective. Moreover, the moderating role of green perceived risk in the formation of green brand image has not been explored, despite the concerns relating to greenwash which have been raised in several green brand studies. Finally, green brand image was found to be a strong antecedent of brand loyalty, besides the predominant elements of green trust and green satisfaction.